Detection of copper ions in an aqueous solution by a dual-peak long period fiber grating functionalized with a polypyrrole–chitosan composite - Li, Yaowei; Liu, Ting; Ge, Kaixin; Gan, Wenbo; Dai, Shixun; Xu, Tiefeng; Zhang, Peiqing (Optics express, 2023)
A dual-peak long period fiber grating (DP-LPFG) sensor functionalized by polypyrrole–chitosan composite was proposed for sensitive detection of Cu 2+ ions in aqueous solution. The nitrogen atom on the polypyrrole ring and the amino group on the chitosan chain in the complex matrix can chelate the Cu 2+ ions. Thus, the refractive index of the overlay changed and further modulated the transmission spectrum of DP-LPFG. After special design, the double peaks can move in opposite directions with the increase of Cu 2+ ion concentration, thereby greatly improving detection sensitivity. The linear sensitivity of the fabricated sensor was measured to be 9.12 and 2.14 nm/ppm (0.61 and 0.14 nm/µM) for concentrations of 0.1–0.5 (1.5 µM-7.5 µM) and 0.5–2 ppm (7.5 µM-30 µM), respectively. In addition, the Langmuir isothermal model was used to evaluate the overall response of the sensor to Cu 2+ ions quantitatively, and the detection limit was determined to be 0.05 ppb (0.75 nM). This ingenious sensor offers a new solution for sensitive detection of heavy metal ions in environmental water.